Deletion of CD38 Suppresses Glial Activation and Neuroinflammation in a Mouse Model of Demyelination - Roboon, Jureepon; Hattori, Tsuyoshi; Ishii, Hiroshi; Takarada-Iemata, Mika; Le, Thuong Manh; Shiraishi, Yoshitake; Ozaki, Noriyuki; Yamamoto, Yasuhiko; Sugawara, Akira; Okamoto, Hiroshi; Higashida, Haruhiro; Kitao, Yasuko; et al. (Frontiers in Cellular Neuroscience, 2019)
CD38 is an enzyme that catalyzes the synthesis of cyclic adenosine diphosphate-ribose from nicotinamide adenine dinucleotide (NAD+). We recently reported that this molecule regulates the maturation and differentiation of glial cells such as astrocytes and oligodendrocytes in the developing brain. To analyze its role in the demyelinating situation, we employed cuprizone (CPZ)-induced demyelination model in mice, which is characterized by oligodendrocyte-specific apoptosis, followed by the strong glial activation, demyelination and repopulation of oligodendrocytes. By using this model, we found that CD38 was upregulated in both astrocytes and microglia after CPZ administration. Experiments using wild-type and CD38 knockout (KO) mice, together with those using cultured glial cells, revealed that CD38 deficiency did not affect the initial decrease of the number of oligodendrocytes, while it attenuated CPZ-induced demyelination and neurodegeneration. Importantly, the clearance of the degraded myelin and oligodendrocyte repopulation were also reduced in CD38 KO mice. Further experiments revealed that these observations were associated with reduced levels of glial activation and inflammatory responses including phagocytosis, most likely through the enhanced level of NAD+ in CD38-deleted condition. Our results suggest that CD38 and NAD+ in the glial cells play a critical role in the demyelination and subsequent oligodendrocyte remodeling through the modulation of glial activity and neuroinflammation.